2022
DOI: 10.3389/fvets.2022.887520
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bovine Tissue-Specific Expressed Genes and Identification of Genetic Variation Within an Adipose Tissue-Specific lncRNA Gene

Abstract: Global classification of bovine genes is important for studies of biology and tissue-specific gene editing. Herein, we classified the tissue-specific expressed genes and uncovered an important variation in the promoter region of an adipose tissue-specific lncRNA gene. Statistical analysis demonstrated that the number of genes specifically expressed in the brain was the highest, while it was lowest in the adipose tissues. A total of 1,575 genes were found to be significantly higher expressed in adipose tissues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Because gene tissue-specific expression is a major cause of differences in the tissue function, therefore, in order to narrow the scope of the target genes, this study predicted miR-204 and miR-181b target genes in cattle adipose tissue-specific genes. A total of 23 adipose tissue-specific genes were screened from different tissues of cattle in the previous study . Targeting prediction revealed that miR-204 and miR-181b have potential binding sites in the 3’ UTR region of Leptin and TRARG1 adipose tissue-specific genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because gene tissue-specific expression is a major cause of differences in the tissue function, therefore, in order to narrow the scope of the target genes, this study predicted miR-204 and miR-181b target genes in cattle adipose tissue-specific genes. A total of 23 adipose tissue-specific genes were screened from different tissues of cattle in the previous study . Targeting prediction revealed that miR-204 and miR-181b have potential binding sites in the 3’ UTR region of Leptin and TRARG1 adipose tissue-specific genes.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure of transcript expression level analysis was consistent with the previously published article. 27 Raw data were filtered to obtain clean reads for analysis. For circRNA sequencing results, the filtered clean reads were mapped to the bovine reference genome (ARS-UCD1.2) using Hisat2 software.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations